2013
DOI: 10.1007/978-3-642-40793-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Does Malware Detection Improve with Diverse AntiVirus Products? An Empirical Study

Abstract: Abstract. We present results of an empirical study to evaluate the detection capability of diverse AntiVirus products (AVs). We used malware samples collected in a geographically distributed honeypot deployment in several different countries and organizations. The malware was collected in August 2012: the results are relevant to recent and current threats observed in the internet. We sent these malware to 42 AVs available from the VirusTotal service to evaluate the benefits in detection from using more than on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The authors also explore if the combination of several AVT can improve protection and showed that AVT diversity and a combination of AVTs indeed improve detection without being able to reach 100% though. Similar empirical analysis using honeypot data [6] brought the same conclusions that diversity improves protection.…”
Section: Related Workmentioning
confidence: 62%
See 1 more Smart Citation
“…The authors also explore if the combination of several AVT can improve protection and showed that AVT diversity and a combination of AVTs indeed improve detection without being able to reach 100% though. Similar empirical analysis using honeypot data [6] brought the same conclusions that diversity improves protection.…”
Section: Related Workmentioning
confidence: 62%
“…In recent studies [6,7,13,14] it is shown that the results have also temporal scale, i.e. AV regression exists, in a way that a given AVT can declare one file as a malware in a given instance of time, but later fail to recognize the file as a malware.…”
Section: Related Workmentioning
confidence: 99%
“…In future work, when we test against more sophisticated attacker data, all of these novel research approaches can be integrated into the SPICE framework as additional layers to test. Studies of using multiple antivirus security products as defense in depth have been conducted such as [21] [22] all showing benefit from combining multiple antivirus engines. These studies are limited to only one layer of defense in depth where with SPICE we expand beyond just antivirus to analyze security products across different layers.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, the vast majority of works use the aggregated results from a collection of antivirus engines as a source of scalable labeling [26]. For example, a common approach to malware detection is antivirus thresholding, in which some minimum number of antivirus engines in a collection must detect a file as malicious in order for it to be considered malware [5,8]. Likewise, plurality and majority voting amongst antivirus engines are popular strategies for performing malware family classification [17,2].…”
Section: Introductionmentioning
confidence: 99%